2022
DOI: 10.3390/life12020239
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Anemic Effect of Antioxidant-Rich Apple Vinegar against Phenylhydrazine-Induced Hemolytic Anemia in Rats

Abstract: This study aims to examine the ability of apple vinegar on phenylhydrazine (PHZ)-induced hemolytic anemia in Wistar rats. In vitro, phenolic and flavonoid content and antioxidant activity were determined. In vivo, phenylhydrazine (10 mg/kg) was injected intravenously into rats for 4 days and then treated with apple vinegar daily by gavage (1 mL/kg) for five weeks. high level of polyphenols and flavonoids (90 ± 1.66 mg GAE/100 mL and 7.29 ± 0.23 mg QE/100 mL, respectively) were found in the apple vinegar which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 80 publications
(98 reference statements)
0
5
0
1
Order By: Relevance
“…These encouraging outcomes are in line with a study that found antioxidant components included in traditional medicinal herbs could increase SOD function. 36 When compared with the normal control group in this investigation, PHZ induction significantly (p < 0.05) decreased serum SOD activity (►Fig. 2C), which may be because superoxide radicals are inhibiting SOD activity.…”
Section: Discussionmentioning
confidence: 56%
“…These encouraging outcomes are in line with a study that found antioxidant components included in traditional medicinal herbs could increase SOD function. 36 When compared with the normal control group in this investigation, PHZ induction significantly (p < 0.05) decreased serum SOD activity (►Fig. 2C), which may be because superoxide radicals are inhibiting SOD activity.…”
Section: Discussionmentioning
confidence: 56%
“…Excessive production of free radicals in the human body can cause such illnesses as cancer, atherosclerosis, Alzheimer’s disease, Parkinson’s disease, and cerebrovascular and cardiovascular diseases. A number of studies have revealed a preventive effect of PCs against these diseases [ 49 , 50 , 51 ]. In vitro systems of cultivation of various plant species can be an alternative source of polyphenolic compounds having a strong antioxidant effect, even stronger than that of intact plants [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ujike et al [ 28 ] and Takatera et al [ 29 ] have reported that apple cider vinegar and citric acid, the primary acids in vinegar, increase iron absorption in the intestine. Ousaaid et al [ 30 ] reported that apple cider vinegar reduces the hemolytic effect of phenylhydrazine in rats with anemia. In addition to these medicinal properties, accessibility to most areas leads to onion, garlic, and apple cider vinegar being candidates for herbal immuno-modulation.…”
Section: Introductionmentioning
confidence: 99%